2009
DOI: 10.1143/apex.2.121502
|View full text |Cite
|
Sign up to set email alerts
|

Organic Thin-Film Transistors with Phase Separation of Polymer-Blend Small-Molecule Semiconductors: Dependence on Molecular Weight and Types of Polymer

Abstract: We have investigated effect of polymer on solution-processed organic thin-film transistors (TFTs) with polymer-blend semiconductors. Organic TFTs made from a solution of 6,13-bis(triisopropylsilylethynyl)-pentacene with a poly(-methylstyrene) (PaMS) molecular weight of 20 k or above, exhibited mobility around 0.1 cm 2 /(VÁs). On the other hand, the organic TFTs with a PaMS molecular weight of 2 k or with a poly(isobutyl methacrylate), exhibited much lower mobility. This can be explained in terms of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 18 publications
(20 reference statements)
2
40
0
Order By: Relevance
“…[33] In particular, differences with regard to the solution's film formation properties are anticipated as viscosity is expected to significantly change with the molecular weight. [35] Therefore, we decided to test solutions with four different molecular weights of polystyrene. [34] These differences have, for instance, been shown in a study on spin-cast devices, where blending with a low molecular weight polymer has not led to vertical stratification of the two components, while higher molecular weights have produced a multilayer structure with good device performance.…”
Section: Optimization Of C8-btbt:polystyrene Blendmentioning
confidence: 99%
“…[33] In particular, differences with regard to the solution's film formation properties are anticipated as viscosity is expected to significantly change with the molecular weight. [35] Therefore, we decided to test solutions with four different molecular weights of polystyrene. [34] These differences have, for instance, been shown in a study on spin-cast devices, where blending with a low molecular weight polymer has not led to vertical stratification of the two components, while higher molecular weights have produced a multilayer structure with good device performance.…”
Section: Optimization Of C8-btbt:polystyrene Blendmentioning
confidence: 99%
“…[184][185][186]193,200,201,203] In contrast, the strong intermolecular interactions made by the rigid conjugated building blocks of polymeric OSC molecules make these molecules less soluble than common insulating polymers such as PS and PMMA. Evaporation of solvent molecules from the film/air interface increases the solute concentration near this interface.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…The effective degrees of polymerization (N i ) in terms of the number of lattice sites were calculated to be 1, 8, 846, and 6 for toluene, PaMS (1 kDa), PaMS (100 kDa), and TIPS, respectively, taking the molecular volume of one solvent molecule to represent one lattice site. Figure 1 shows the ternary phase diagram calculated for M PaMS = 1 kDa, for which no (considerable) phase separation was observed during casting, [9,10] and M PaMS = 100 kDa, for which extensive phase separation during spin-coating was demonstrated. [10] Upon spin-coating a typical blend solution (f 1 % 0.99) the volume of the solvent rapidly decreases, which, beyond a critical value, quenches the system into the coexistence region yielding two phases, defined by the binodal compositions.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Besides processing conditions and substrate effects, also molecular parameters determine whether the desired phase-separated morphology is obtained. For poly(a-methylstyrene)/triisopropylsilylpentacene (PaMS/TIPS) O-TFT blends, for instance, several authors [9,10] reported vertical phase separation into a layered geometry in ascast films for sufficiently high molecular weight of PaMS (of the order of 10 2 kDa). In contrast, for low PaMS molecular weights (of the order of 1 kDa) phase separation and significant TIPS crystallization was only obtained after subsequent annealing at T > T g .…”
Section: Introductionmentioning
confidence: 99%